Our Friend Hedgehog : The Story of Us - Castillo, Lauren (New York : Alfred A. Knopf, 2020)
When a storm separates Hedgehog from her lifelong friend, Mutty, she bravely sets out to find him and makes some very good new friends in the process.
"A Junior Library Guild Selection"--Dust jacket.
Ages 5-9.
Grades 2-3.
Keywords: Best friends -- Juvenile fiction; Friendship -- Juvenile fiction; Hedgehogs -- Juvenile fiction; Animals -- Juvenile fiction; Best friends -- Fiction; Friendship -- Fiction; Hedgehogs -- Fiction; Animals -- Fiction